2023
DOI: 10.1002/cpp.2900
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of individual schema therapy in older adults with borderline personality disorder: A multiple‐baseline case series design

David A. Khasho,
Sebastiaan P. J. van Alphen,
Machteld A. Ouwens
et al.

Abstract: ObjectiveThe aim of this study was to explore the effectiveness of schema therapy (ST) in older adults with borderline personality disorder (BPD).MethodsMultiple baseline case series design with five BPD patients, with a mean age of 66. After a baseline phase with random length, patients received weekly ST sessions for a year, followed by follow‐up sessions during 6 months. Participants rated the credibility of negative core beliefs weekly; various secondary outcome measures were assessed every 6 months (sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…2020) were selected, and together with the participant, the most representative negative core belief regarding the EMS was selected using the downward arrow technique (Khasho et al. 2023; Videler et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2020) were selected, and together with the participant, the most representative negative core belief regarding the EMS was selected using the downward arrow technique (Khasho et al. 2023; Videler et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Participants determined three negative core beliefs in short statements together with the researcher during the inclusion interview. The three highest scoring EMS of the Young Schema Questionnaire 3 Short Form (YSQ-S3; Rijkeboer et al 2020) were selected, and together with the participant, the most representative negative core belief regarding the EMS was selected using the downward arrow technique (Khasho et al 2023;Videler et al 2018). The credibility of these negative core beliefs was rated weekly on a 100-point visual analogue scale (VAS), ranging from 0 to 100.…”
Section: Primary Outcome Measurementioning
confidence: 99%
“…Results revealed that 30 sessions of group schema therapy resulted in significant improvements with medium to large effect sizes after 2 years for avoidant and dependent personality disorder, but results for obsessive-compulsive personality disorder are inconclusive. In the study of Khasho et al (2023), the effectiveness of schema therapy was investigated in older adults with borderline personality disorder using a multiple baseline case series design. Results revealed that schema therapy led to a significant decrease in negative core beliefs.…”
mentioning
confidence: 99%